129 Validating a new dependency measurement for parkinson's disease. Issue 12 (14th November 2019) - Ramsay, Neil; Macleod, Angus; Counsell, Carl
Abstract : Introduction: Functional dependency is a key outcome in Parkinson's disease (PD). We created an algorithm to dichotomously assess dependency in PD patients, based on the Unified Parkinson's disease rating scale (UPDRS) part 2, routinely collected in PD studies. Methods: We defined dependency from items of UPDRS Part 2 (i.e. hygiene, dressing, feeding, getting out of chair and walking). We validated this algorithm using dependency data from 1113 patients from 6 community-based incidence PD cohorts. We also validated against indirect measures relating to cognition, quality of life and motor impairment. Results: Our algorithm showed high specificity and sensitivity (specificity 94% and sensitivity 70% at baseline; 90% and 84% respectively at 5 years). We found evidence for construct validity with poorer MMSE and quality of life scores in dependent patients. Discussion: We have validated a algorithm to dichotomously assess dependency in PD patients, which can be widely used in research studies.